New species of Lepidocyrtus Bourlet and Entomobrya Rondani (Collembola: Entomobryoidea: Entomobryidae) from Brazil - Bellini, Bruno C.; Cipola, Nikolas G.; Godeiro, Nerivânia N. (Zootaxa, 2015)
The taxonomic comprehension of Brazilian entomobryids had several contributions during the last decade, but the absence of detailed chaetotaxic schemes to most of endemic species difficult identifications and probably hides undescribed species in surveys across the country. Herein we describe two new species of the family and provide detailed dorsal chaetotaxy of them, in hope to guide future identifications and descriptions within the genera in Brazil and Neotropical Region. Lepidocyrtus sotoi sp. nov. is possibly more related to L. biphasis due to the lack of antennal and leg scales, but presents a unique dorsal head chaetotaxy among the Neotropical species of the genus. Entomobrya bahiana sp. nov. presents an uncommon color pattern and dorsal chaetotaxy in Th. II–III, Abd. II and IV when compared to other Entomobrya spp. from Neotropical Region.